Pb center dot center dot center dot pi aryl interactions as supramolecular synthons - Tiekink, E.R.T.; Zukerman-Schpector, J. (CSIRO Publishing, 2010)
A survey of lead (Pb) structures containing Pb center dot center dot center dot pi aryl interactions has been conducted. Such contacts usually lead to zero- or one-dimensional aggregates with rare examples of two- and three-dimensional architectures. The Pb center dot center dot center dot pi aryl interactions are found only in crystal structures containing lead(II) centres and arise as a result of electron donation of the lead-bound lone pair of electrons to the lowest unoccupied molecular orbital of the accepting aryl ring. The prevalence of Pb center dot center dot center dot pi interactions as a supramolecular synthon is relatively low, occurring in similar to 3% of all structures containing lead and at least one aryl ring, but these are more likely to form compared with Sn center dot center dot center dot pi interactions.